Perancangan Pembangkit Listrik Tenaga Air Mini Dengan Turbin Spiral - sayuna, jeri imanuel; Sanusi, Arifin; Bale, Jefri S. (Universitas Nusa Cendana, 2024)
Mini power plants certainly need water energy as the main ingredient. Although the source of electrical energy is already quite large in Indonesia, but in the countryside it is not fully able to enjoy it, many we often find along rural roads, especially in rice fields with very minimal lighting available. The use of water as irrigation of course we can also use as a hydroelectric power plant on a small scale, by utilizing the existing water flow we can make small-scale power generation equipment that adjusts the amount of irrigation water flow of rice fields. Therefore, the results of research on making mini hydroelectric power plants with the VDI 2222 method for street lighting in rice fields can be useful in the community. This tool has the same principle